2011
DOI: 10.1111/j.1369-1600.2010.00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimmune regulation of alcohol consumption: behavioral validation of genes obtained from genomic studies

Abstract: Analysis of mouse brain gene expression, using strains that differ in alcohol consumption, provided a number of novel candidate genes that potentially regulate alcohol consumption. We selected six genes [beta-2-microglobulin (B2m), cathepsin S (Ctss), cathepsin F (Ctsf), interleukin 1 receptor antagonist (Il1rn), CD14 molecule (Cd14) and interleukin 6 (Il6)] for behavioral validation using null mutant mice. These genes are known to be important for immune responses but were not specifically linked to alcohol c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
212
2
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(231 citation statements)
references
References 61 publications
13
212
2
4
Order By: Relevance
“…Validating several candidate genes from these studies (including Cd14, Il1ra, and Il6) through single-gene null mutations in mice confirmed that knockout of each gene resulted in decreased alcohol consumption on a two-bottle choice test (Blednov et al, 2012). In humans, polymorphisms with genes encoding for IL-1β, IL-1RN, IL-10, and other immune-related genes have been associated with alcohol dependence, the functional impact of these allelic variants generally supporting a link between increased pro-inflammatory signaling and increased susceptibility to alcoholism (Marcos et al, 2008;Pastor et al, 2005).…”
Section: Alcohol Glia and Neuroimmune Signalingmentioning
confidence: 86%
“…Validating several candidate genes from these studies (including Cd14, Il1ra, and Il6) through single-gene null mutations in mice confirmed that knockout of each gene resulted in decreased alcohol consumption on a two-bottle choice test (Blednov et al, 2012). In humans, polymorphisms with genes encoding for IL-1β, IL-1RN, IL-10, and other immune-related genes have been associated with alcohol dependence, the functional impact of these allelic variants generally supporting a link between increased pro-inflammatory signaling and increased susceptibility to alcoholism (Marcos et al, 2008;Pastor et al, 2005).…”
Section: Alcohol Glia and Neuroimmune Signalingmentioning
confidence: 86%
“…A large body of evidence supports the role of GABAergic transmission and its interaction with neuroimmune mechanisms that include TLR4, in alcohol dependence and its effects (Alfonso-Loeches et al, 2010;Pascual et al, 2011;Blednov et al, 2012;Crews and Vetreno, 2014;Bajo et al, 2014). Alcohol releases endogenous ligands for TLR4 in the brain (Crews et al, 2013) and knockout of the TLR4 accessory protein CD14 interferes with the ability of LPS to increase alcohol drinking in wild-type mice (Blednov et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the ventral pallidum (VP), which is implicated in drug abuse decisions, voluntary excessive drinking is regulated by the a1 subunits Yang et al, 2011), but human clinical linkage studies support a role for the a2 subunits in alcohol dependence (Edenberg, 2012). A large body of evidence indicates that neuroimmune (including Toll-like receptor 4 (TLR)) signaling contributes to reward-system activity and is associated with alcohol dependence and the effects of alcohol, and postmortem human studies correlate neuroimmune gene expression with lifetime alcohol consumption (Crews et al, 2011;Pascual et al, 2011;Blednov et al, 2012;Crews and Vetreno, 2014). However, the relationship of the neuroimmune signals to the GABA A subunits and the initiation of binge drinking by previously naive individuals is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Metaanalyses of gene expression studies in alcohol preferring strains of mice and postmortem tissue from human alcoholics revealed dysregulation of neuroimmune and neuroinflammatory signaling pathways [151]. Null mutant mice for six of these dys regulated immune candidate genes (B2m, Ctsf, Ctss, Il1rn, Cd14 and Il6 ) showed reduced voluntary alco hol intake and preference [151]. The findings from this study validate the use of genomic analysis for identi fying functional groups of genes that regulate alcohol consumption and, in doing so, indicated a novel role for neuroimmune signaling in controlling drinking.…”
Section: Neuroimmune Signalingmentioning
confidence: 99%